Ensuring safety and functionality of electroglottography measurements during dynamic pulmonary MRI. Issue 5 (24th November 2015) - Özen, Ali Caglar; Traser, Louisa; Echternach, Matthias; Dadakova, Tetiana; Burdumy, Michael; Richter, Bernhard; Bock, Michael
Abstract : Purpose: To combine vocal tract measurements with dynamic MRI of the lungs to provide fundamental insights into the lung physiology during singing. Methods: To analyze vocal fold oscillatory patterns during dynamic lung MRI, an electroglottography (EGG) system was modified to allow for simultaneous EGG measurements during MR image acquisitions. A low‐pass filter was introduced to suppress residual radiofrequency (RF) coupling into the EGG signal. RF heating was tested in a gel phantom to ensure MR safety, and functionality of the EGG device was assessed in a volunteer experiment at singing frequencies from A5 to A3. In the recorded EGG signals, remaining RF interferences were removed by independent component analysis post processing, and standard EGG parameters such as fundamental frequency, contact quotient and jitter were calculated. In a second volunteer experiment, EGG recordings were compared with lung diameter measurements from 2D time‐resolved trueFISP acquisitions. Results: RF heating measurements resulted in less than 1.2°C temperature increase in the gel phantom. EGG parameters measured during MR imaging are within the range of ideal values. In the lung measurement, both the lung diameter and the EGG recordings could be successfully performed with only minimal interference. Conclusion: EGG recording is pos sible during dynamic lung MRI, and glottal activity can be studied safely at 1.5T. Magn Reson Med 76:1629–1635, 2016. © 2015 International Society for Magnetic Resonance in Medicine